Charge delocalization mode and change in aromaticity of protonated 7‐phenylbenzo[k]fluoranthenes studied by experimental observation and DFT calculations. (19th July 2019) - Okazaki, Takao; Matsunaga, Takuya; Kitagawa, Toshikazu
Abstract: 7‐Phenylbenzo[ k ]fluoranthene (4 ), which is one of non‐alternant polycyclic aromatic hydrocarbons, was protonated at the C(12) position in neat CF3 SO3 H to give a persistent carbocation (4aH + ). The cation was successfully observed by NMR measurements at rt. The most deshielded protons were observed as doublet signals at 8.92 and 8.71 ppm for H(1) and H(3). The most deshielded 13 C signals appeared at 184.4 and 176.6 ppm for C(12a) and C(7). The positive charge was found to be delocalized to four carbons in a 1‐naphthalenium unit and to two other carbons according to Δδ 13 C from4 to4aH + . DFT calculations indicated that4aH + was the most stable among possible protonation carbocations. The NICS(1) zz values of4aH + suggested that the five‐membered π‐ring is nonaromatic and that the other benzenoid rings are aromatic. The influence of the 7‐phenyl group on aromaticity and on positive charge delocalization was limited. The next most stable cations were computed to be cations (4bH + and4cH + ) that were generated by the protonation at the C(3) and C(4) positions, respectively. Their Gibbs energies were similar within 0.7 kcal/mol to that of4aH + . Their five‐membered π‐rings were proved to be anti‐aromatic according to the NICS(1) zz criteria.4bH + and4cH + can be depicted by canonical structures with a cyclopentadienyl cation unit, which is suggested to be responsible for their anti‐aromaticity. Abstract : 7‐Phenylbenzo[ k ]fluoranthene (4 ), which is one of non‐alternant polycyclic aromatic hydrocarbons, was protonated at the C(12) position in neat CF3 SO3 H to give a persistent carbocation (4aH + ). The cation was successfully observed by NMR measurements at rt. NICS(1) zz values of4aH + suggested that the five‐membered ring was nonaromatic and that the other benzenoid rings were aromatic.